2021
DOI: 10.3390/ijms22063180
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Antiplatelet Therapy: Important Considerations and Future Perspectives

Abstract: Lipids play an essential role in platelet functions. It is known that polyunsaturated fatty acids play a role in increasing platelet reactivity and that the prothrombotic phenotype plays a crucial role in the occurrence of major adverse cardiovascular events. The ongoing increase in cardiovascular diseases’ incidence emphasizes the importance of research linking lipids and platelet function. In particular, the rebound phenomenon that accompanies discontinuation of clopidogrel in patients receiving dual antipla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Lipoproteins can influence platelet count and characteristics and modulate the risk of atherothrombosis via the megakaryocyte-platelet hemostatic axis ( 34 ). In the present study it was found that HDL was a protective factor for the occurrence of CR in children with KD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipoproteins can influence platelet count and characteristics and modulate the risk of atherothrombosis via the megakaryocyte-platelet hemostatic axis ( 34 ). In the present study it was found that HDL was a protective factor for the occurrence of CR in children with KD.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study found that low HDL levels were associated with CR in CAD patients ( 36 ). Moreover, it was shown that patients with low HDL levels might be more prone to platelet hyperreactivity in the period after clopidogrel cessation ( 34 ), and the infusion of reconstituted HDL was highly effective in inhibiting platelet hyperactivity in diabetic patients ( 37 ). However, a study of ACS patients undergoing PCI suggested that HDL was inversely associated with platelet activation parameters but not with clopidogrel response variability ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysophosphatidylethanolamine (lysoPE) is a lysophospholipid that is a deacylated product of phosphatidylethanolamine (PE) hydrolysis induced by phospholipase A1/A2 [ 1 ]. LysoPE is a minor component of the cell membrane [ 2 ] and stimulates chemotactic migration and infiltration of ovarian cancer cells [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aims of our study were (1) to investigate the physiological functions of lysoPE, targeting its effect on lipid accumulation in human hepatocytes; (2) to explore the modulation of intracellular lipid metabolism, including the changes in lipid content and the alterations of molecular composition and (3) to analyze the expression of the genes related to lipid metabolism and catabolism. The graphical representation of the present study workflow is shown in the supplementary data (Scheme S1).…”
Section: Introductionmentioning
confidence: 99%